Constitutional Question Mechanisms in Various Countries: Formulation of Constitutional Rights Protection in the Indonesian Judicial System - Daniel NP Tampubolon (JURNAL ILMIAH DETUBUYA, 2026)
This study examines the urgency of implementing a constitutional question mechanism in the Indonesian judicial system to strengthen the protection of citizens' constitutional rights. The main problem identified is a legal gap in which general court judges are often forced to apply laws they deem unconstitutional because they lack the authority to suspend cases. This condition creates a paradox of justice, leading to legal but unconstitutional decisions. This study uses a normative legal research method and a comparative legal approach to examine the judicial systems of Germany, South Korea, and France. The results show that the constitutional question mechanism functions as a golden bridge to harmonize the judicial dualism between the Supreme Court and the Constitutional Court. The proposed solution is to reconstruct procedural law by granting judges the authority to raise constitutional questions directly to the Constitutional Court in concrete cases. The main findings confirm that this mechanism can transform the protection of citizens' rights from a passive to an active, immanent role in every adjudication process. In conclusion, the adoption of constitutional questions is an absolute requirement for Indonesia to realize substantial constitutional supremacy and guarantee a single legal certainty for justice seekers.